Privatisation Methods and Economic Growth in Transition Economies - John Bennett; Saul Estrin; James Maw; Giovanni Urga (Fondazione Eni Enrico Mattei (FEEM), 2004)
We investigate the impact of differences in privatisation method on national economic performance in transition economies. Our approach is to estimate, using dynamic panel data methods, a growth equation over 23 countries for the period 1990-2001. Among our results, we find that mass privatisation has significant positive effect on growth across a wide variety of definitions and specifications. This result holds with particular force after 1995, i.e., once the period of early transition and recession was over. Our analysis suggests that an advantage of mass privatisation was that it led spontaneously to development of the capital market, which is significantly correlated with economic growth.
Keywords: L33; O40; P27; P31; 330; Privatization; Method; Economic Growth; Transition; Privatisierung; Wirtschaftswachstum; Aktienmarkt; Transformationsstaaten